1,3,5-Triazine Nitrogen Mustards with Different Peptide Group as Innovative Candidates for AChE and BACE1 Inhibitors - Dawid Maliszewski; Agnieszka Wróbel; Beata Kolesińska; Justyna Frączyk; Danuta Drozdowska (Molecules, 2021)
A series of new analogs of nitrogen mustards (4a–4h) containing the 1,3,5-triazine ring substituted with dipeptide residue were synthesized and evaluated for the inhibition of both acetylcholinesterase (AChE) and β-secretase (BACE1) enzymes. The AChE inhibitory activity studies were carried out using Ellman’s colorimetric method, and the BACE1 inhibitory activity studies were carried out using fluorescence resonance energy transfer (FRET). All compounds displayed considerable AChE and BACE1 inhibition. The most active against both AChE and BACE1 enzymes were compounds A and 4a, with an inhibitory concentration of AChE IC50 = 0.051 µM; 0.055 µM and BACE1 IC50 = 9.00 µM; 11.09 µM, respectively.